The challenge of self-governance in complex, globalizing economies: Collection of revised papers of a PhD seminar - Elinor Ostrom; Achim Schlüter (Albert-Ludwigs-Universität Freiburg, Institut für Forstökonomie, 2007)
Table of Contents: Floriane Clement: A Multi-Scale Analysis of Institutions, Interestsand Beliefs Associated With Forest Policies. Insights from NorthernVietnam; Katrin Daedlow, Robert Arlinghaus, Volker Beckmann: Collective Choice on Different Spatial Levels and over Time: A Framework to Analyze Adaptation and Sustainability of Common Pool Resource Management in German Recreational Fisheries (GRF); Eva Ebenhöh: Designing Agent-Based Models of Water Management Regimes Using the IAD Framework; Louisa Evans: Local Decision-Making Processes for Governance of Marine Social-Ecological Systems; Adam Henry: Simulating the Evolution of Policy-Relevant Beliefs: Can Rational Learning Lead to Advocacy Coalitions?; Alexander Lenger: Constitutional Ecological Economics; Achim Schlüter: Institutional Change, Rationalities and Thick Description; Christine Werthmann: Water Management in Seasonal Floodplains of the Mekong Delta; Stefan Ambec, Carine Sebi: Acceptable Regulations to Reduce Resource Extraction with Heterogeneous Costs; Bjorn Vollan: What Reciprocity? – The Impact of Culture and Sociopolitical Background on Trust Games in Namibia and South Africa
Keywords: 330